Cu2ZnSnSe4: How Far Does Off‐Stoichiometry Go?. Issue 17 (30th April 2018) - Gurieva, Galina; Ferreira, Rafael; Knoll, Philipp; Schorr, Susan
Abstract : Polycrystalline powder samples of eight very far off‐stoichiometric Cu2 ZnSnSe4 (CZTSe) compounds (off‐stoichiometry types A–D) are grown using the solid‐state reaction method in evacuated silica tubes. An additional thermal annealing is performed, in order to study the influence of annealing on the phase content and stoichiometry of the CZTSe phases formed under these conditions. The structural characterization of the synthesized materials before as well as after annealing is carried out by powder X‐ray diffraction (PXRD), paying a special attention to the possibility of minimization the content of secondary phases. Wavelength dispersive X‐ray spectroscopy (WDX) is used to determine the chemical composition of the obtained phases, paying a special attention to the phase constituents as well as the evolution of the CZTSe phases after the additional annealing. A comparative study of the phase content of very far off‐stoichiometric CZTSe compounds is presented. The possible limits of the existence region of the kesterite CZTSe are discussed. Abstract : Polycrystalline powder samples of very far off‐stoichiometric Cu2 ZnSnSe4 (CZTSe) compounds are analyzed paying a special attention to the secondary phases content. Results appear to show potential limits to the existence of the kesterite phase. since none of the compositions measured have crossed outside the boundaries of Cu/(Zn+Sn) = 0.6–1.7, Zn/Sn = 0.5–1.6 within the resolution of the WDX method.